2010
DOI: 10.1099/mic.0.035881-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline growth pH on the expression of cell envelope proteins in Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum is a Gram-negative anaerobic organism that plays a central role in the development of periodontal diseases. The progression of periodontitis is associated with a rise in pH of the gingival sulcus which promotes the growth and expression of virulence factors by periodontopathic bacteria. We have previously reported that the expression of specific cytoplasmic proteins is altered by a shift in growth pH. In the present study we have compared cell envelope protein expression of F. nucleatum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
1
25
2
1
Order By: Relevance
“…The increased intracellular concentration of TRAP transporters and increased concentration of ABC transporter binding proteins could be considered to be energy conserving as TRAP transporters rely on proton-motive force instead of ATP hydrolysis (ABC transporters) to drive the uptake of solutes from the environment. In contrast to our results, the production of TRAP transporter binding proteins was suppressed 10-fold in planktonic cells cultured at pH 7.8 [27]. The authors explained that the decreased abundance of TRAP binding proteins in planktonic cells may be due to a reduced proton gradient [27].…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The increased intracellular concentration of TRAP transporters and increased concentration of ABC transporter binding proteins could be considered to be energy conserving as TRAP transporters rely on proton-motive force instead of ATP hydrolysis (ABC transporters) to drive the uptake of solutes from the environment. In contrast to our results, the production of TRAP transporter binding proteins was suppressed 10-fold in planktonic cells cultured at pH 7.8 [27]. The authors explained that the decreased abundance of TRAP binding proteins in planktonic cells may be due to a reduced proton gradient [27].…”
Section: Resultscontrasting
confidence: 99%
“…Earlier studies in our laboratory showed that the regulation of proteins associated with energy production, transport and protein folding occurred in planktonic cells cultured at pH 7.8 [26,27]. While the present study reports a similar change in protein expression patterns at pH 8.2, we have identified 32 proteins that are altered in response to growth at pH 8.2.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations